(untitled) (Swiss Medical Weekly, 2026)
Hypokalaemia is an electrolyte imbalance frequently encountered among patients in the emergency department (ED), often resulting from acute medical conditions or medication side effects. Given its potential to significantly impact morbidity and mortality, timely recognition, accurate diagnosis, and individualised management are essential, especially in ED settings. Common aetiologies of hypokalaemia include diuretic therapy and gastrointestinal losses, such as vomiting and diarrhoea. Management strategies, including the choice of potassium supplementation, should be guided by the severity of hypokalaemia and the presence of associated adverse effects. This article aims to equip ED physicians with a comprehensive understanding of hypokalaemia management, facilitating informed, patient-specific decisions in the dynamic environment of emergency care.